Discovering Comfortable Driving Strategies Using Simulation-Based Multiobjective Optimization - Dovgan, E.; Tušar, T.; Javorski, M.; Filipič, B. (Informatica)
Discovering Comfortable Driving Strategies Using Simulation-Based Multiobjective Optimization